(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the success rate of prophylactic antibiotic therapy in elective cesarean section, to describe some factors related to the indication of prophylactic antibiotic therapy in cesarean section at Bac Giang Obstetrics and Pediatrics Hospital. Research subjects and methods: Cross-sectional descriptive study, conducted on 3188 patients using prophylactic antibiotics; data analysis and processing using SPSS 20.0 software. Results: The success rate was 99.94% and all groups of antibiotics used for postoperative treatment were used as prophylactic antibiotics. Conclusion: Using prophylactic antibiotics in cesarean section is extremely important to ensure the health of patients and reduce costs and human resources in treatment.